Multidisciplinary Real-Time Model for Smart Agriculture using Internet of Things - Ajitesh Kumar, Mona Kumari (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
IoT is a network or a web of physical objects that contain an embedded technology for sensing and interacting with surroundings. It plays a prominent role in almost every sector, like retail, education, manufacturing, safety, and security. One of the best applications is in the field of agriculture, which the authors will propose in this research work. It will help in optimizing the production by analyzing and monitoring various data produced by the sensors. Here IoT will run parallel with other technology like Cloud, Big data, data analytics, and wireless sensor network. The combination of these technologies will result in precision farming. It will lead to the most significant contribution to the agriculture IoT market during the time of forecasting. The model will help us to analyze the information related to weather conditions like temperature, humidity, rain, and many more. Based on this information farmer will take action accordingly. Some time due to climate change and lack of information available may all result in reduced productivity. The authors propose a real-time model that will enhance the productivity level, cost, and efficiency.